Access to Housing and Social Inclusion in a Post-Crisis Era: Contextualizing Recent Trends in the City of Athens - Maloutas, Thomas (2020)
The way housing affordability evolved since WW2 in Greece—and in its capital city in particular—is an example of how the South European welfare system managed, for several decades, to provide socially inclusive housing solutions without developing the services of a sizeable welfare state until global forces and related policies brought it to an end. The increased role of the market in housing provision since the 1980s, the rapid growth of mortgage lending in the 1990s, the neoliberal policy recipes imposed during the crisis of the 2010s and the unleashed demand for housing in the aftermath of the crisis have led to increased housing inequalities and converged the outcome of this South European path with the outcome of undoing socially inclusive housing solutions provided by the welfare state in other contexts. The article follows longstanding and recent developments concerning the housing model in Greece and especially in the city of Athens, focusing on mechanisms that have allowed access to affordable housing for broad parts of the population during different historical periods, and examines the extent to which the current housing model remains inclusive or not. The aim here is to discuss the most important challenges concerning access to decent housing and highlight the need for inclusive housing policies to be introduced into the current social and political agenda.